1983
DOI: 10.1177/31.4.6298307
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin (ACTH) and the N-terminal fragment of pro-opiomelanocortin are located in the same granules in cells of rat pituitary gland.

Abstract: The localization of corticotropin (ACTH) and of the Nterminal fragment (NTF) of pro-opiomelanocortin were assessed by light and electron microscope immunochemistry. Using the unlabeled technique of Sternberger at the light microscope level, a strongly positive reaction for both NTF and ACTH antisera was observed in all secretory cells of the pars intermedia. In the pars distalis, immunostaining with ACTH antiserum was localized in stellate cells dispersed throughout the lobe. As observed in serial, consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Immunohistochemical studies showed a co-localized distribution of two or more of the POMC-derived peptides in the same corticotropic and melanotropic cells of the anterior and intermediate lobe of the pituitary, and in the POMC neurons in the basal hypothalamus, at the light and electron microscopical level (Akil et al, 1978;Bloch et al, 1978Bloch et al, , 1979Crine et al, 1978;Dub6 et al, 1978;Sofroniew, 1979;Weber et al, 1979;Chatelain et al. 1979;Nilaver et al, 1979;Vaudri et al, 1980;Guy et al, 1980;Loh et al, 1982;Cantin et al, 1983;Stoeckel et al, 1983Stoeckel et al, , 1985Mains et al, 1983;Tanaka and Kurosumi, 1986;Powel and Baker, 1987;Kantin et al, 1988). Pelletier and Leclerc (1979) have shown at the ultrastructural level that ACTH is present in dense-core secretory granules in the brain.…”
Section: Co-localization Of Pomc Derived Peptidesmentioning
confidence: 99%
“…Immunohistochemical studies showed a co-localized distribution of two or more of the POMC-derived peptides in the same corticotropic and melanotropic cells of the anterior and intermediate lobe of the pituitary, and in the POMC neurons in the basal hypothalamus, at the light and electron microscopical level (Akil et al, 1978;Bloch et al, 1978Bloch et al, , 1979Crine et al, 1978;Dub6 et al, 1978;Sofroniew, 1979;Weber et al, 1979;Chatelain et al. 1979;Nilaver et al, 1979;Vaudri et al, 1980;Guy et al, 1980;Loh et al, 1982;Cantin et al, 1983;Stoeckel et al, 1983Stoeckel et al, , 1985Mains et al, 1983;Tanaka and Kurosumi, 1986;Powel and Baker, 1987;Kantin et al, 1988). Pelletier and Leclerc (1979) have shown at the ultrastructural level that ACTH is present in dense-core secretory granules in the brain.…”
Section: Co-localization Of Pomc Derived Peptidesmentioning
confidence: 99%